Communicable disease associated with milk and dairy products in England and Wales 1951-80. Issue 6331 (12th June 1982) - Galbraith, N S; Forbes, P; Clifford, C
Abstract : In England and Wales between 1951 and 1980 233 reported outbreaks of communicable disease attributed to milk or dairy products affected nearly 10 000 people, of whom four died. Tuberculosis and brucellosis have been controlled, but milk-borne outbreaks of salmonellosis and campylobacter enteritis due to raw or defectively pasteurised milk are common and may be increasing in number. Universal heat treatment of milk is an effective preventive measure, and it is regrettable that the continued sale of untreated milk is to be permitted in England and Wales.